Speech Genre: A Study of Gossip in Australian English Speaking Context - Nurhadi Hamka (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
A gossip as a casual conversation usually occurs in diverse context or a wide range of social situations; has distinct and various topics; and involve an irregular set of participants. The scholars scrutinize that conversation has highly structured activity of which people tacitly realize that there are some basic conventions to follow – such as when to speak or to stay silent and to listen. In this study, I specifically discuss one of the speech genre – a gossip, in Australia English speaking context. The gossip data of the study is taken from the research conducted by Thornburry, Scott, and Slade, Diana (2006). In a discussion, I focus the analysis of the generic structure of the gossip and how it establishes the social function (within) the speech members. Several findings conveyed that: 1) there is a leeway of shifting from one genre to another – e.g. narrative to gossip, within the same participants; 2) conversation can be successful if all the participants aware of and follow the basic conventions – when to talk or to listen, support to judgement or reluctant to the focus of conversation; 3) the genre, e.g. narrative or gossip, could motivate people to leave or to join the conversation which then could establish and reinforce the group membership and maintain the values of the social group.